The effect of filtered nanoparticles on gas filtration efficiency of granular activated carbons. (September 2017) - Kim, Changhyuk; Lee, Handol; Juelfs, Adam; Haynes, Christy L.; Pui, David Y.H.
Abstract: Granular activated carbons (GACs) are widely used porous materials for removing gaseous contaminants in the air. In addition, GACs can work as pack-bed filters for removing particles. However, the filtered particles may block the pores of GACs, which are capture sites for gaseous contaminants, and reduce their gas filtration efficiency. In this study, the effect of the filtered particles on GAC gas filtration efficiency was investigated by measuring toluene penetration through GACs when nanoparticles were simultaneously introduced to the GACs. The nanoparticles were generated from toluene molecules through soft X-ray assisted gas-to-particle conversion and mixed in-situ with toluene molecules. The penetration of toluene through the GACs was determined by measuring the volume distribution of nanoparticles, which were converted from toluene molecules downstream of the GACs. By integrating the measured volume distribution of the nanoparticles, the total volume concentration of nanoparticles was calculated and plotted as a function of time. The time-resolved penetration of toluene remained the same regardless of the particle filtration by the GACs. Moreover, the GACs with different granule sizes had same time-resolved penetration of toluene. These experimental results showed that GACs can be used to remove nanoparticles and gas contaminants simultaneously without changing their gas filtration efficiency. Graphical abstract: